2021
DOI: 10.1111/ddi.13374
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate fire severity diversity promotes richness of forest carnivores in California

Abstract: Aim Fire can strongly influence ecosystem function, and human activities are disrupting fire activity at the global scale. Ecological theory and a growing body of literature suggest that a mixed severity fire regime promotes biodiversity in western North America. Some researchers advocate the use of pyrodiversity (i.e. heterogeneity in aspects of the fire regime such as time since fire or severity) as a conservation index to be maximized. Others caution against this approach arguing that the index oversimplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 96 publications
2
7
0
Order By: Relevance
“…While larger carnivores (e.g., mountain lion and black bear) decreased their occupancy and intensity of use in burned areas, we observed that several medium-sized species increased their activity (e.g., coyotes) and occupancy (e.g., gray fox and wild boar) of burned areas. These results mirror the response of mesopredators to wildfire observed in similar studies within California (Schuette et al, 2014;Jennings et al, 2016;Furnas et al, 2021). Predation mode may also modify how certain predators respond to severe fire in woodlands.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While larger carnivores (e.g., mountain lion and black bear) decreased their occupancy and intensity of use in burned areas, we observed that several medium-sized species increased their activity (e.g., coyotes) and occupancy (e.g., gray fox and wild boar) of burned areas. These results mirror the response of mesopredators to wildfire observed in similar studies within California (Schuette et al, 2014;Jennings et al, 2016;Furnas et al, 2021). Predation mode may also modify how certain predators respond to severe fire in woodlands.…”
Section: Discussionsupporting
confidence: 80%
“…We predicted that canopy cover, time since burn, elevation, and landscape ruggedness would be associated with occupancy and animal activity across our species assemblage. Independent of fire, elevation and ruggedness are important factors in shaping mammal habitat selection in similar ecosystems (Poley et al, 2014;Furnas et al 2021). Canopy cover is also an important predictor of mammal habitat use (Allen et al 2015;Bose et al, 2018) and canopy cover loss following fire serves as an important proxy for fire severity in the burned areas of our study site.…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…By contrast, feral cats actively selected fire scars, but only those created by high‐severity, rather than mild fires, and only fire scars that were recent (<9 months old) (McGregor et al ., 2014), thus demonstrating how both fire severity and age can be important. In California, USA, carnivore species richness was highest at intermediate levels of fire severity diversity (Furnas, Goldstein & Figura, 2022).…”
Section: How and Why Do Predators Respond To Fire?mentioning
confidence: 99%
“…The available literature primarily focuses on bipartite interactions (but see Geary et al ., 2018), but we know that predators and prey live and operate within complex trophic networks. Recent work has examined how carnivore communities respond to fire (Jorge et al ., 2020; Furnas et al ., 2022; Gigliotti et al ., 2022), but there has been little focus on interactions between multiple predator and prey species. A key area for future development is understanding how fire alters networks of interactions between predators and consumers (e.g.…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%
“…Yet, despite the strong potential for these shifts in fire regimes to affect vertebrate communities, we have limited information on how vertebrate wildlife is affected by changes in forest fire size and severity, much less the mechanisms that drive these effects and how they may vary across functional groups (Jones & Tingley, 2021). In particular, determining the effects of fire severity on forest vertebrates is critical both because of the needs for their conservation and for the many roles they play in regulating plant communities, forest regeneration, trophic structure, and other ecosystem functions (Furnas et al, 2021; Morrison et al, 2012; Volkmann et al, 2020). Specifically, studies on high‐severity fire effects on mammals are needed: a recent meta‐analysis on fire‐prone forests of the US found only two studies of high‐severity fire impacts on small mammals, despite the roles that small mammals play in forest ecosystems (Fontaine & Kennedy, 2012).…”
Section: Introductionmentioning
confidence: 99%